Dynamic аrchetypes оf еmotions аs tools of psychotherapeutic work: the "Stimulus, Emotion, Type" мethod - Vaskivska, Svitlana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
B a c k g r o u n d . The article substantiates the idea of the author’s method of express diagnosis and psychotherapeutic study of a typical human emotional response: "Stimulus, Emotion, Type" (SET). The technology involves the interpretation of emotions as evolutionarily formed dynamic archetypes of adaptation, which makes it possible to gain a deeper understanding of the content of the client’s conflict reactions and effectively transform them. M e t h o d s . As a result of theoretical generalization and empirical research, nine typical modes-archetypes of human experiences were identified: Dramatization, Avoidance, Caution, Dependence, Isolation, Rivalry, Research (Awareness), Expansion, Balanced Acceptance of Reality. In the methodology, they are represented by a deck of associative cards with an indication of emotions that replace the basic experience, and a card that reveals their archetypal characteristics. Projecting the client’s current emotions onto the map of the evolutionary unfolding of modes of experience helps to establish an archaically condensed action and predict its course. R e s u l t s . The essential reading of an individual pattern of experiences allows you to quickly distance the client from tense emotional states, decipher the symbolism of the leading archetypal experience, and discuss a strategy and tactics for solving the problem that are more effective for this conflict situation. С o n c l u s i o n . The productivity of the method was confirmed in the process of mathematical and statistical analysis of the results of empirical research and proved practically. SET technology is an effective tool for developing algorithms for psychotherapeutic work.